Optimizing NK Cell-Based Immunotherapy in Myeloid Leukemia: Abrogating an Immunosuppressive Microenvironment - Kaweme, Natasha Mupeta; Zhou, Fuling (Frontiers in Immunology, 2021)
Natural killer (NK) cells are prominent cytotoxic and cytokine-producing components of the innate immune system representing crucial effector cells in cancer immunotherapy. Presently, various NK cell-based immunotherapies have contributed to the substantial improvement in the reconstitution of NK cells against advanced-staged and high-risk AML. Various NK cell sources, including haploidentical NK cells, adaptive NK cells, umbilical cord blood NK cells, stem cell-derived NK cells, chimeric antigen receptor NK cells, cytokine-induced memory-like NK cells, and NK cell lines have been identified. Devising innovative approaches to improve the generation of therapeutic NK cells from the aforementioned sources is likely to enhance NK cell expansion and activation, stimulate ex vivo and in vivo persistence of NK cells and improve conventional treatment response of myeloid leukemia. The tumor-promoting properties of the tumor microenvironment and downmodulation of NK cellular metabolic activity in solid tumors and hematological malignancies constitute a significant impediment in enhancing the anti-tumor effects of NK cells. In this review, we discuss the current NK cell sources, highlight ongoing interventions in enhancing NK cell function, and outline novel strategies to circumvent immunosuppressive factors in the tumor microenvironment to improve the efficacy of NK cell-based immunotherapy and expand their future success in treating myeloid leukemia.